Valuing Care Work : Comparative Perspectives - Benoit, Cecilia M., 1954-; Hallgrimsdóttir, Helga, 1969- (Book collections on Project MUSE., 2011)
"To trace the relationships between gender, labour, and equity in health care, the essays in this volume analyse the rules and practices that shape care work. The contributors highlight how national configurations of the welfare state shape the gendering of paid and unpaid intimate labour in a range of settings and discuss how the policies and practices associated with neoliberalism have focussed on efficiency and accountability to the detriment of other policy agendas, including those that might further increase dignity and equity for both recipients and providers of paid and unpaid health care."--Pub. desc.